Magnetic field pitch angle and perpendicular velocity measurements from multi-point time-delay estimation of poloidal correlation reflectometry. (28th December 2016) - Prisiazhniuk, D; Krämer-Flecken, A; Conway, G D; Happel, T; Lebschy, A; Manz, P; Nikolaeva, V; Stroth, U
Abstract: In fusion machines, turbulent eddies are expected to be aligned with the direction of the magnetic field lines and to propagate in the perpendicular direction. Time delay measurements of density fluctuations can be used to calculate the magnetic field pitch angle α and perpendicular velocity v ⊥ profiles. The method is applied to poloidal correlation reflectometry installed at ASDEX Upgrade and TEXTOR, which measure density fluctuations from poloidally and toroidally separated antennas. Validation of the method is achieved by comparing the perpendicular velocity (composed of the E × B drift and the phase velocity of turbulence v ⊥ = v E × B + v p h ) with Doppler reflectometry measurements and with neoclassical v E × B calculations. An important condition for the application of the method is the presence of turbulence with a sufficiently long decorrelation time. It is shown that at the shear layer the decorrelation time is reduced, limiting the application of the method. The magnetic field pitch angle measured by this method shows the expected dependence on the magnetic field, plasma current and radial position. The profile of the pitch angle reproduces the expected shape and values. However, comparison with the equilibrium reconstruction codecliste suggests an additional inclination of turbulent eddies at the pedestal position (2–3°). This additional angle decreases towards the core and at the edge.